Contribuição para o desenvolvimento de compósito cimento-madeira com materiais da região amazônica - FONSECA, Fábio de Oliveira (Universidade Federal do Pará, 2011)
This work intends to propose an application for tropical wood waste from wood industry as saw dust; from the region of Belem, in the fabrication of wood-cement composite. Due to the natural chemical incompatibility between wood and cement, this procedure results in a set retarding effect, with wood specie depending intensity. This by-effect can be beaten by using a procedure like additives, wood mineralization, accelerated carbonation and others. Analysis were made with axial compression strength at 28 days age data, for mortars made with 2, 3.5 and 5% wood content in mass; using cements type CP I and CP II; with and without Calcium Clorets-based set accelerator additive. Then, obtained data were statistically analyzed for evaluation on wood content and additive use over mechanical resistance. Most of existing researches uses reforesting species, being the tropical ones almost never studied. So, this work represents a pioneer effort in developing a cement-bonded wood composite with our regionally available materials and residues.